Endogenous and exogenous miR-520c-3p modulates CD44-mediated extravillous trophoblast invasion. (February 2017) - Takahashi, Hironori; Ohkuchi, Akihide; Kuwata, Tomoyuki; Usui, Rie; Baba, Yosuke; Suzuki, Hirotada; Chaw Kyi, Tha Thu; Matsubara, Shigeki; Saito, Shigeru; Takizawa, Toshihiro
Abstract: Introduction: Adequate extravillous trophoblast (EVT) invasion is essential for successful placentation. Although miR-520c-3p plays an important role in CD44-mediated invasion in cancer cells, there is little information on whether miR-520c-3p is involved in the regulatory mechanisms of CD44-mediated EVT invasion. Methods: We screened first trimester trophoblast cells and trophoblast cell lines for expression of miR-520c-3p using real-time polymerase chain reaction. The cell invasion assay was performed using EVT cell lines, HTR8/SVneo and HChEpC1b, to investigate the capability of suppressing EVT invasion by miR-520c-3p . Laser microdissection analysis was then used to determine whether miR-520c-3p was present in the first trimester decidua. Finally, the possibility of chorionic villous trophoblast (CVT)-EVT communication via exosomal miR-520c-3p was determined using an in vitro model based on BeWo exosomes and the EVT cell lines as recipient cells. Results: The miR-520c-3p level was significantly downregulated in EVT cell lines and EVTs. Cell invasion was significantly inhibited in miR-520c-3p -overexpressing cell lines, involving a significant reduction of CD44. Laser microdissection analysis showed that miR-520c-3p in the periarterial area of the decidua was significantly higher than that in the non-periarterial area. Using an in vitro model system, BeWo exosomal miR-520c-3p was internalized into the EVT cells with subsequently reduced cell invasion via CD44 repression. Conclusions: EVT invasion is synergistically enhanced by the reciprocal expression of endogenous miR-520c-3p and CD44. The present study supports a novel model involving a placenta-associated miRNA function in cell-cell communication in which CVT exosomal miR-520c-3p regulates cell invasion by targeting CD44 in EVTs. Highlights: Adequate EVT invasion is essential for successful placentation. CD44-mediated invasion was one of possible mechanisms for EVT invasion. miR-520c-3p played an important role in the regulation of CD44-mediated EVT invasion. The downregulation of endogenous miR-520c-3p accelerated EVT invasion via CD44. Villous trophoblast miR-520c-3p can potentially modulate EVT invasion via exosomes.